(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): Which factors motivate children and adults to learn? Purpose: The purpose of the research is to identify factors that motivate children and adults to learn. Method: The data were obtained by the qualitative method, whereas the compilation method was used to summarize the results of other authors concerning the topic, the comparative method was used for comparing individual factors among children and adults and the deductive method was used to form general statements on the basis of individual examples. Results: The research shows that motivational factors for education among children differ from those among adults. The children’s motivation to learn is more influenced by intrinsic and extrinsic factors from the immediate environment (parents, school, peers etc.). Adults are influenced by their careers directing them towards the need for new knowledge, which is why most of the factors are linked to career development. Organization: It is important for organizations to be aware of the importance of motivational factors for education and try to motivate their employees to educate themselves as much as possible, because this is also a way to improve their knowledge base. The same applies to schools that play an important role in motivating children to learn. Society: The theoretical background guides the society towards directing more attention to and being more aware of the importance of motivational factors for education among children and adults. Originality: The research is original, because the review article provides a theoretical basis for encouraging motivation among children and adults. Limitations/Future Research: For a broader view of motivational factors for education, more literature would have to be examined and a comparison of factors that influence motivation for education in other age groups prepared.